Wear-resistant lubricating oil and preparation method thereof

By using PAO synthetic oil, ester-gravitated sesame oil-sucrose esters and other components in lubricating oil to form a three-layer protection structure, the problem of lack of performance in existing lubricating oil under harsh conditions has significantly improved the resistance and flow of anti-wear and flow. Variety performance extends the life of the equipment and reduces energy consumption.

CN119372009APending Publication Date: 2025-01-28SUMACH CHEM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411581021.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing lubricating oils are difficult to maintain good lubricating and protective performance under harsh working conditions such as high temperature, high pressure, and high speed, resulting in increased wear of equipment, increased energy consumption and shortened service life. At the same time, the interaction between additives is complex and difficult to predict and control. .

Method used

A wear-resistant lubricant, its raw materials including PAO synthetic oil, ester-gravic sesame oil-sucrose ester, consolidated phenol, sulfulin aminophyty molybdenonate, sulfide isotylene, zinc phosphate, and calcium sulfonate, and calcium And nano graphene composite combination cluster, the interaction of these components forms a unique three -layer protection structure, and improves the resistance and flow of lubricating oil.

Benefits of technology

It significantly improves the abrasion resistance and flow of lubricating oil, extended the service life of the equipment, reduced energy consumption and operating temperature, improved the reliability and safety of the equipment, and solved the problem of additive interaction. Diversify stability and decrease in friction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372009A_ABST
    Figure CN119372009A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lubricating oil, in particular to wear-resistant lubricating oil and a preparation method thereof. Comprising the following raw materials: PAO (poly alpha olefin) synthetic oil, esterified castor oil-sucrose ester, octyl phenol, molybdenum dithiocarbamate, sulfurized isobutylene, zinc dialkyl dithiophosphate, calcium sulfonate and a nano graphene composite comb copolymer. In the lubricating system, esterified castor oil-sucrose ester molecules and a copolymer side chain form hydrophobic interaction through a hydrophobic end, and a hydrogen bond is formed between a hydrophilic end and the surface of the nano graphene, so that the rheological property and the dispersion stability are enhanced. The system forms a three-layer protection structure: a bottom layer provides bearing capacity by a nano graphene sheet layer, a middle layer forms a surface protection layer by esterified castor oil-sucrose ester molecules, and a top layer forms an elastic network by a copolymer side chain. In order to solve the problem that esterified castor oil-sucrose ester and a copolymer interfere with each other, octyl phenol is introduced as a compatibility improver, and the overall performance is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lubricating oil, and in particular to a wear-resistant lubricating oil and a preparation method thereof. Background Art

[0002] In the context of the rapid development of modern industry, lubricating oil, as a key medium for the operation of various mechanical equipment, has become increasingly important. Although traditional lubricating oil plays a role in basic lubrication and cooling, as industrial equipment continues to develop towards high speed, heavy load, intelligence, and miniaturization, its lubrication and protection performance under extreme working conditions has gradually become insufficient, making it difficult to meet the requirements of modern industry for long life, high reliability, and high efficiency of equipment. Especially under harsh working conditions such as high temperature, high pressure, and high speed, traditional lubricating oil is prone to oxidative degradation, resulting in a decrease in lubrication performance and an inability to provide long-lasting and effective protection for equipment, which ultimately causes problems such as increased equipment wear, increased energy consumption, and shortened service life.

[0003] Wear-resistant lubricants can form a protective tribochemical film with self-repairing ability on the metal friction surface by adding special wear-resistant additives to the base oil, significantly improving the load-bearing capacity and anti-wear performance of the lubricant. This protective film can not only effectively reduce the direct contact and wear of the metal surface, but also repair the existing microscopic wear to a certain extent, thereby greatly extending the service life of the equipment. At the same time, due to the reduction of friction loss, wear-resistant lubricants can also significantly improve the energy utilization efficiency of equipment, reduce operating temperature, and reduce maintenance frequency and maintenance costs. In addition, the excellent extreme pressure performance of wear-resistant lubricants enables it to maintain good lubrication effect under heavy load conditions, effectively prevent sudden failures of equipment, and improve the reliability and safety of equipment.

[0004] However, the development of high-performance wear-resistant lubricants faces many technical difficulties and challenges. The most prominent one is the complex interaction between various additives. The interaction mechanism is complex and diverse, and it is difficult to accurately predict. For example, some extreme pressure additives and antioxidants will react chemically, resulting in a significant decrease in the efficacy of the two additives; some dispersants will compete with metal detergents for adsorption, reducing the cleaning and dispersion effect; some friction modifiers will also interfere with the process of wear-resistant additives forming a protective film on the metal surface, which will in turn increase the wear of the equipment. The antagonistic effect between these additives will not only weaken their respective performance, but also produce unexpected negative effects, such as accelerating oil oxidation, promoting metal corrosion, and increasing sludge deposition. Summary of the invention

[0005] (1) Technical issues to be resolved The purpose of the present invention is to provide a wear-resistant lubricating oil and a preparation method thereof, so as to improve the load-bearing capacity and anti-wear performance of the lubricating oil and solve the problem of interaction between additives.

[0006] (2) Technical solution To achieve the above-mentioned object, on the one hand, the present invention provides a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 50-55 parts of PAO (polyalphaolefin) synthetic oil, 8-10 parts of esterified castor oil-sucrose ester, 3-5 parts of octylphenol, 2-3 parts of molybdenum dithiocarbamate, 3-4 parts of sulfided isobutylene, 2-3 parts of zinc dialkyl dithiophosphate, and 2-3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex having both hydrophilic and hydrophobic properties, formed by connecting the carboxyl group of the esterified castor oil and the hydroxyl group of the sucrose ester through an esterification reaction.

[0007] Furthermore, the wear-resistant lubricating oil further comprises, by weight, 2 to 4 parts of a nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0008] Furthermore, the preparation method of the nano-graphene composite comb-like copolymer comprises: S11. washing methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with 5% sodium hydroxide solution to obtain washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, drying the washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with anhydrous magnesium sulfate to obtain dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, and distilling the dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate under reduced pressure to obtain purified dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate; S12. The purified methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate were dissolved in tetrahydrofuran to obtain a first solution, azobisisobutyronitrile was added to the first solution to obtain a second solution, nitrogen was introduced into the second solution, and the reaction was carried out at 65 to 75 ° C for 24 to 36 hours to obtain a first reaction solution; S13. The first reaction solution is poured into an excess of cold ether to precipitate to obtain a first precipitate, and the first precipitate is vacuum dried to obtain a comb-like copolymer; S14. Adding flake graphite to a mixture of concentrated sulfuric acid and concentrated nitric acid to obtain a second mixed solution, slowly adding KMnO4 to the second mixed solution under ice bath conditions to obtain a second reaction solution, reacting the second reaction solution at 35-45 ° C for 2-3 h, then heating to 95-105 ° C for 30-40 min to obtain a third reaction solution, adding deionized water and hydrogen peroxide to the third reaction solution to terminate the reaction, and obtaining a fourth reaction solution; S15. centrifuging the fourth reaction solution to obtain a centrifuged reaction solution, washing the centrifuged reaction solution to neutrality to obtain a washed reaction solution, and ultrasonicating the washed reaction solution to obtain graphene oxide; S16. Disperse graphene oxide in tetrahydrofuran and ultrasonically treat it for 2 to 3 hours to obtain a graphene dispersion, dissolve the comb-like copolymer in tetrahydrofuran to obtain a comb-like copolymer solution, slowly drop the comb-like copolymer solution into the graphene dispersion to obtain a total dispersion, first ultrasonically disperse the total dispersion for 30 to 40 minutes to obtain a total dispersion after ultrasonication, magnetically stir the total dispersion after ultrasonication for 12 to 24 hours to obtain a total dispersion after magnetic stirring, filter the total dispersion after magnetic stirring to obtain a product, and vacuum dry the product to obtain a nano-graphene composite comb-like copolymer.

[0009] Furthermore, the preparation method of the esterified castor oil-sucrose ester comprises: S21. The castor oil is dried under vacuum at 60-70°C for 4-5h to obtain dried castor oil; S22. The dried castor oil was added to a three-necked flask, and then a 30 wt % KOH methanol solution was added to obtain a first mixed solution, nitrogen was introduced, and the first mixed solution was reacted at 65 to 75 ° C and 400 to 500 rpm for 4 to 5 h to obtain a first reaction solution; S23. The first reaction solution was cooled to room temperature, petroleum ether was added for extraction to obtain an extracted first reaction solution, the extracted first reaction solution was washed with distilled water for 3 to 4 times to obtain a washed first reaction solution, the washed first reaction solution was dried with anhydrous sodium sulfate to obtain a dried first reaction solution, the dried first reaction solution was rotary evaporated to obtain esterified castor oil; S24. The esterified castor oil is dissolved in dichloromethane to obtain an esterified castor oil solution, and sucrose ester is added to the esterified castor oil solution at a temperature of -5 to 0°C to obtain a second mixed solution; S25. In the second mixed solution, N, N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in dichloromethane were slowly added dropwise, stirred at 0 ° C for 1 h to obtain a third mixed solution, and the third mixed solution was heated to room temperature and the reaction was continued for 24 to 36 h to obtain a second reaction solution; S26. The second reaction liquid is subjected to reduced pressure distillation to obtain a second reaction liquid after reduced pressure distillation, the second reaction liquid after reduced pressure distillation is purified by column chromatography, the stationary phase is silica gel, and the mobile phase is petroleum ether / ethyl acetate to obtain a purified product, the purified product is rotary evaporated to obtain a rotary evaporated product, and the rotary evaporated product is vacuum dried to obtain the final product, i.e., esterified castor oil-sucrose ester.

[0010] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a wear-resistant lubricating oil, which is applied to the aforementioned plastic pipe containing plant fibers, comprising the following steps: S31. The PAO (poly alpha olefin) synthetic oil was added to the reactor, heated to 60 ~ 70 ° C, stirring speed of 1000 ~ 1500rpm, to obtain pretreated PAO (poly alpha olefin) synthetic oil, the pretreated PAO (poly alpha olefin) synthetic oil was vacuum treated for 10 ~ 15min to obtain vacuum treated PAO (poly alpha olefin) synthetic oil; S32. Esterified castor oil - sucrose ester and octylphenol are sequentially added to the vacuum treated PAO (poly alpha olefin) synthetic oil, and stirred at 65 to 70 ° C and 1000 to 1500 rpm for 30 to 35 min to obtain a first mixed solution; S33. Molybdenum dithiocarbamate and isobutylene sulfide were sequentially added to the first mixed solution, and stirred at 80 to 85 ° C, 1500 to 2000 rpm for 30 to 35 min to obtain a second mixed solution; S34. Zinc dialkyl dithiophosphate and calcium sulfonate were sequentially added to the second mixed solution, and stirred at 80 to 85 ° C and 2000 to 2500 rpm for 30 to 35 min to obtain a third mixed solution; S35. Adding the nanographene composite comb copolymer to the third mixed solution, ultrasonically treating at 70 to 75° C. and 3000 to 4000 rpm for 15 to 30 min to obtain a fourth mixed solution; S36. In the fourth mixed solution, vacuum treatment is performed at 70 to 75° C. and 1500 to 2000 rpm for 15 to 20 min to obtain a vacuum-treated solution; S37. Cool the vacuum-treated solution to 45-50° C. to obtain a cooled solution, filter the cooled solution through a 100-mesh filter to obtain a sieved solution, and allow the sieved solution to stand for 24-36 hours to obtain a wear-resistant lubricating oil.

[0011] The mechanism of action of the above raw material components is as follows: PAO (polyalphaolefin) synthetic oil: As a base oil, its molecular structure is highly regular, which not only provides excellent low-temperature fluidity and good viscosity-temperature characteristics to ensure stable lubrication performance over a wide temperature range, but also has high oxidation stability to effectively reduce oil degradation, and the regularity of the chemical structure can significantly reduce evaporation losses.

[0012] Esterified castor oil-sucrose ester: After the esterification reaction, the hydroxyl group (-OH) of castor oil is converted into fatty acid ester group (-COOR), which improves thermal stability and lubricity; while sucrose ester undergoes esterification reaction with the carboxylic acid (-COOH) of esterified castor oil through its hydroxyl group (-OH) to form an ester bond (-COO-) link, so that the hydrophilic sucrose ester part is combined with the hydrophobic esterified castor oil part to form an amphiphilic complex structure with both hydrophilic and hydrophobic properties. With its unique amphiphilic molecular structure, it forms a stable molecular layer at the interface. Its hydrophilic end can form a hydrogen bond with the surface of the nanomaterial, and the hydrophobic end has good compatibility with the oil phase to enhance the dispersion stability. This characteristic enables it to form an orderly molecular film structure on the friction surface and provide effective lubrication.

[0013] Octylphenol: Its molecular structure significantly improves the compatibility between the components. It can effectively inhibit the tendency of micelle formation and provide continuous antioxidant properties during the lubrication process, playing a key role in regulating the strength of the interface.

[0014] Molybdenum dithiocarbamate: It can generate MoS2 protective film in situ on the friction surface. This protective film can not only significantly reduce the friction coefficient of the system, but also provide excellent anti-wear performance for the friction pair.

[0015] Sulfurized isobutylene: As an extreme pressure anti-wear additive, it can form a protective film on the friction surface under high temperature and high pressure conditions. This protective film not only enhances the strength of the oil film, but also significantly improves the load-bearing capacity of the lubrication system.

[0016] Zinc dialkyl dithiophosphate: It can form a stable zinc phosphate protective film on the metal friction surface. This protective film not only provides continuous antioxidant properties for the system, but also effectively prevents corrosion on the metal surface.

[0017] Calcium sulfonate: Through its excellent cleaning and dispersing properties and acid neutralization ability, it effectively prevents sludge from depositing in the system, thereby maintaining the long-term stability of the entire lubrication system.

[0018] Nanographene composite comb copolymer: It forms a unique physical barrier layer in the lubricating oil. Its special structure not only significantly improves the system's load-bearing capacity and rheological properties, but also enhances the dispersion stability. The entanglement of its side chains also provides continuous elastic protection for the system.

[0019] (3) Beneficial effects Compared with the prior art, the present invention has the following beneficial effects: 1. Through the dual stabilization mechanism of esterified castor oil-sucrose ester molecules, the hydrophilic end forms hydrogen bonds with the surface of nanographene, and the hydrophobic end forms hydrophobic interactions with the side chains of the copolymer. Octylphenol is introduced to reduce the tendency of micelle formation and conformational interference of the copolymer, thereby solving the interaction problem between additives.

[0020] 2. A unique three-layer protection structure is formed. The bottom layer is composed of nano-graphene, which forms a dense layered structure through π-π stacking to provide high mechanical strength. The middle layer is composed of esterified castor oil-sucrose ester arranged vertically to fill the surface micro-concavities and convexities and provide a deformable lubrication effect of the molecular chain. The top layer is composed of copolymers to form a three-dimensional network structure, which provides elastic cushioning and energy absorption and rebound characteristics, thereby improving the anti-wear performance of the lubricant. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the wear-resistant lubricating oil of Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The test equipment and preparations of the examples described below are as follows: Electronic balance (Sartorius, Germany), electric blast constant temperature dryer (Shanghai Fomar Experimental Equipment), stainless steel reactor (Shanghai Laibei), electric constant temperature water bath (Jiangsu Kedao), rotary evaporator (Shanghai Dalo Scientific Instrument), pulverizer (Shandong Tianfang Machinery), magnetic stirrer (Shanghai Meiyingpu), centrifuge (Guangzhou Jidi), ultrasonic instrument (Xi'an Bohui), vacuum drying oven (Nanjing Zairanliucheng), pH meter (Hangzhou Liance); chemicals and reagents were purchased from Sigma-Aldrich.

[0024] Example 1: This example discloses a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 52 parts of PAO (polyalphaolefin) synthetic oil, 10 parts of esterified castor oil-sucrose ester, 3 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through an esterification reaction. The wear-resistant lubricating oil, by weight fraction, also comprises: 4 parts of nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0025] In this lubricating system, the hydrophobic ends of the esterified castor oil-sucrose ester molecules and the copolymer side chains are hydrophobic, and they will spontaneously aggregate together to form a stable hydrophobic interaction. At the same time, the hydrophilic ends of the esterified castor oil-sucrose ester molecules form hydrogen bonds with the oxygen-containing functional groups on the surface of nanographene. This dual effect enhances the rheological properties of the system and improves the dispersion stability of nanographene in the oil phase. On this basis, the lubricant forms a unique three-layer protection structure: first, the bottom layer is composed of nanographene sheets, which are rich in π electrons and can form a strong interaction force with the metal surface. At the same time, a compact layered structure is formed through π-π stacking; because graphene has extremely high mechanical strength and a special two-dimensional layered structure, it can not only effectively disperse the load, but its compactly stacked layered structure can also slip between layers under the action of shear force, thereby providing excellent load-bearing capacity. Secondly, the middle layer is composed of esterified castor oil-sucrose ester molecules. These molecules rely on their amphiphilic structure, that is, the hydrophilic end is bound to the graphene surface through hydrogen bonds, and the hydrophobic end points to the oil phase. Driven by the intermolecular force, they form an oriented arrangement perpendicular to the surface. This structure can not only fill the microscopic bumps on the metal surface, but also the deformability of its molecular chain provides a lubricating effect, effectively reducing the direct contact of the friction surface. Finally, the top layer is formed by the flexible side chains of the copolymer molecules through physical entanglement to form a three-dimensional network structure. This is because the copolymer molecular chain is flexible and can perform creeping motion, allowing different molecular chains to interweave and entangle with each other. This structure can absorb energy through the stretching, deformation and rearrangement of the molecular chain under the action of external force. When the load is reduced, it can be restored to its original state through the rebound of the molecular chain, thereby providing continuous elastic buffer protection. However, this system also has some problems: when the esterified castor oil-sucrose ester interacts with the copolymer side chain, it will cause the copolymer conformation to change and reduce the degree of intermolecular entanglement; at the same time, the micelles formed by the esterified castor oil-sucrose ester will wrap the nanographene composite comb-like copolymer molecules and reduce its contact area with the oil phase. To solve these problems, the lubricant introduces octylphenol as a compatibility improver, which interacts with the nanographene composite comb-like copolymer side chain through the hydrophobic group and reduces the micelle formation tendency of the esterified castor oil-sucrose ester, effectively reducing the interference of the esterified castor oil-sucrose ester on the copolymer conformation, thereby optimizing the performance of the entire lubrication system, such as Figure 1 shown.

[0026] The preparation method of the nano-graphene composite comb-shaped copolymer comprises: S11. washing methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with 5% sodium hydroxide solution to obtain washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, drying the washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with anhydrous magnesium sulfate to obtain dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, and distilling the dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate under reduced pressure to obtain purified dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate; S12. The purified methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate were dissolved in tetrahydrofuran to obtain a first solution, azobisisobutyronitrile was added to the first solution to obtain a second solution, nitrogen was introduced into the second solution, and the reaction was carried out at 65 to 75 ° C for 24 to 36 hours to obtain a first reaction solution; S13. The first reaction solution is poured into an excess of cold ether to precipitate to obtain a first precipitate, and the first precipitate is vacuum dried to obtain a comb-like copolymer; S14. Adding flake graphite to a mixture of concentrated sulfuric acid and concentrated nitric acid to obtain a second mixed solution, slowly adding KMnO4 to the second mixed solution under ice bath conditions to obtain a second reaction solution, reacting the second reaction solution at 35-45 ° C for 2-3 h, then heating to 95-105 ° C for 30-40 min to obtain a third reaction solution, adding deionized water and hydrogen peroxide to the third reaction solution to terminate the reaction, and obtaining a fourth reaction solution; S15. centrifuging the fourth reaction solution to obtain a centrifuged reaction solution, washing the centrifuged reaction solution to neutrality to obtain a washed reaction solution, and ultrasonicating the washed reaction solution to obtain graphene oxide; S16. Disperse graphene oxide in tetrahydrofuran and perform ultrasonic treatment for 2 to 3 hours to obtain a graphene dispersion, dissolve the comb-like copolymer in tetrahydrofuran to obtain a comb-like copolymer solution, slowly drop the comb-like copolymer solution into the graphene dispersion to obtain a total dispersion, first ultrasonically disperse the total dispersion for 30 to 40 minutes to obtain a total dispersion after ultrasonication, magnetically stir the total dispersion after ultrasonication for 12 to 24 hours to obtain a total dispersion after magnetic stirring, filter the total dispersion after magnetic stirring to obtain a product, and vacuum dry the product to obtain a nano-graphene composite comb-like copolymer.

[0027] The preparation method of the esterified castor oil-sucrose ester comprises: S21. The castor oil is dried under vacuum at 60-70°C for 4-5h to obtain dried castor oil; S22. The dried castor oil was added to a three-necked flask, and then a 30 wt % KOH methanol solution was added to obtain a first mixed solution, nitrogen was introduced, and the first mixed solution was reacted at 65 to 75 ° C and 400 to 500 rpm for 4 to 5 h to obtain a first reaction solution; S23. The first reaction solution was cooled to room temperature, petroleum ether was added for extraction to obtain an extracted first reaction solution, the extracted first reaction solution was washed with distilled water for 3 to 4 times to obtain a washed first reaction solution, the washed first reaction solution was dried with anhydrous sodium sulfate to obtain a dried first reaction solution, the dried first reaction solution was rotary evaporated to obtain esterified castor oil; S24. The esterified castor oil is dissolved in dichloromethane to obtain an esterified castor oil solution, and sucrose ester is added to the esterified castor oil solution at a temperature of -5 to 0°C to obtain a second mixed solution; S25. In the second mixed solution, N, N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in dichloromethane were slowly added dropwise, stirred at 0 ° C for 1 h to obtain a third mixed solution, and the third mixed solution was heated to room temperature and the reaction was continued for 24 to 36 h to obtain a second reaction solution; S26. The second reaction liquid is subjected to reduced pressure distillation to obtain a second reaction liquid after reduced pressure distillation, the second reaction liquid after reduced pressure distillation is purified by column chromatography, the stationary phase is silica gel, and the mobile phase is petroleum ether / ethyl acetate to obtain a purified product, the purified product is rotary evaporated to obtain a rotary evaporated product, and the rotary evaporated product is vacuum dried to obtain the final product, i.e., esterified castor oil-sucrose ester.

[0028] A method for preparing a wear-resistant lubricating oil, applied to the aforementioned wear-resistant lubricating oil, comprises the following steps: S31. The PAO (poly alpha olefin) synthetic oil was added to the reactor, heated to 60 ~ 70 ° C, stirring speed of 1000 ~ 1500rpm, to obtain pretreated PAO (poly alpha olefin) synthetic oil, the pretreated PAO (poly alpha olefin) synthetic oil was vacuum treated for 10 ~ 15min to obtain vacuum treated PAO (poly alpha olefin) synthetic oil; S32. Esterified castor oil - sucrose ester and octylphenol are sequentially added to the vacuum treated PAO (poly alpha olefin) synthetic oil, and stirred at 65 to 70 ° C and 1000 to 1500 rpm for 30 to 35 min to obtain a first mixed solution; S33. Molybdenum dithiocarbamate and isobutylene sulfide were sequentially added to the first mixed solution, and stirred at 80 to 85 ° C, 1500 to 2000 rpm for 30 to 35 min to obtain a second mixed solution; S34. Zinc dialkyl dithiophosphate and calcium sulfonate were sequentially added to the second mixed solution, and stirred at 80 to 85 ° C and 2000 to 2500 rpm for 30 to 35 min to obtain a third mixed solution; S35. Adding the nanographene composite comb copolymer to the third mixed solution, ultrasonically treating at 70 to 75° C. and 3000 to 4000 rpm for 15 to 30 min to obtain a fourth mixed solution; S36. In the fourth mixed solution, vacuum treatment is performed at 70 to 75° C. and 1500 to 2000 rpm for 15 to 20 min to obtain a vacuum-treated solution; S37. Cool the vacuum-treated solution to 45-50° C. to obtain a cooled solution, filter the cooled solution through a 100-mesh filter to obtain a sieved solution, and allow the sieved solution to stand for 24-36 hours to obtain a wear-resistant lubricating oil.

[0029] Embodiment 2: A wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 55 parts of PAO (polyalphaolefin) synthetic oil, 10 parts of esterified castor oil-sucrose ester, 5 parts of octylphenol, 3 parts of molybdenum dithiocarbamate, 4 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through esterification reaction. The wear-resistant lubricating oil, by weight fraction, also comprises: 4 parts of nanographene composite comb copolymer; the comb copolymer in the nanographene composite comb copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0030] The preparation methods of the nanographene composite comb-shaped copolymer and esterified castor oil-sucrose ester in this embodiment are the same as those in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is the same as that in Example 1.

[0031] Embodiment 3: This wear-resistant lubricating oil comprises the following raw materials in parts by weight: 50 parts of PAO (polyalphaolefin) synthetic oil, 8 parts of esterified castor oil-sucrose ester, 3 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 2 parts of zinc dialkyl dithiophosphate, and 2 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through esterification reaction. The wear-resistant lubricating oil, by weight fraction, also comprises: 2 parts of nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0032] The preparation methods of the nanographene composite comb-shaped copolymer and esterified castor oil-sucrose ester in this embodiment are the same as those in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is the same as that in Example 1.

[0033] Embodiment 4: A wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 53 parts of PAO (polyalphaolefin) synthetic oil, 9 parts of esterified castor oil-sucrose ester, 4 parts of octylphenol, 2.5 parts of molybdenum dithiocarbamate, 3.5 parts of sulfided isobutylene, 2.5 parts of zinc dialkyl dithiophosphate, and 2.5 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through esterification reaction. The wear-resistant lubricating oil, by weight fraction, also comprises: 3 parts of nanographene composite comb copolymer; the comb copolymer in the nanographene composite comb copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0034] The preparation methods of the nanographene composite comb-shaped copolymer and esterified castor oil-sucrose ester in this embodiment are the same as those in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is the same as that in Example 1.

[0035] Embodiment 5: A wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 54 parts of PAO (polyalphaolefin) synthetic oil, 8 parts of esterified castor oil-sucrose ester, 5 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 4 parts of sulfided isobutylene, 2 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through esterification reaction. The wear-resistant lubricating oil, by weight fraction, also comprises: 3 parts of nanographene composite comb copolymer; the comb copolymer in the nanographene composite comb copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0036] The preparation methods of the nanographene composite comb-shaped copolymer and esterified castor oil-sucrose ester in this embodiment are the same as those in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is the same as that in Example 1.

[0037] Control group 1: This embodiment differs from embodiment 1 in that the nano-graphene composite comb-like copolymer is not contained.

[0038] The present embodiment discloses a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 52 parts of PAO (polyalphaolefin) synthetic oil, 10 parts of esterified castor oil-sucrose ester, 3 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex having both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through an esterification reaction.

[0039] The preparation method of the esterified castor oil-sucrose ester in this embodiment is consistent with that in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is consistent with that in Example 1.

[0040] Control group 2: This embodiment differs from embodiment 1 in that it does not contain esterified castor oil-sucrose ester.

[0041] This embodiment discloses a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 52 parts of PAO (polyalphaolefin) synthetic oil, 3 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate. The wear-resistant lubricating oil, by weight fraction, also comprises: 4 parts of nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0042] The preparation method of the nanographene composite comb-like copolymer of this embodiment is consistent with that of embodiment 1. The preparation method of a wear-resistant lubricating oil of this embodiment is consistent with that of embodiment 1.

[0043] Control group 3: This embodiment differs from embodiment 1 in that octylphenol is not contained.

[0044] This embodiment discloses a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 52 parts of PAO (polyalphaolefin) synthetic oil, 10 parts of esterified castor oil-sucrose ester, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate; the esterified castor oil-sucrose ester is an amphiphilic complex with both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of esterified castor oil and the hydroxyl group of sucrose ester through esterification reaction. The wear-resistant lubricating oil, by weight fraction, also includes: 4 parts of nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0045] The preparation methods of the nanographene composite comb-shaped copolymer and esterified castor oil-sucrose ester in this embodiment are the same as those in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is the same as that in Example 1.

[0046] Control group 4: This embodiment discloses a wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 52 parts of PAO (polyalphaolefin) synthetic oil, 10 parts of esterified castor oil, 3 parts of octylphenol, 2 parts of molybdenum dithiocarbamate, 3 parts of sulfided isobutylene, 3 parts of zinc dialkyl dithiophosphate, and 3 parts of calcium sulfonate. The wear-resistant lubricating oil, by weight fraction, also comprises: 4 parts of nanographene composite comb-like copolymer; the comb-like copolymer in the nanographene composite comb-like copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

[0047] The preparation method of the esterified castor oil and nanographene composite comb-shaped copolymer in this embodiment is consistent with that in Example 1. The preparation method of a wear-resistant lubricating oil in this embodiment is consistent with that in Example 1.

[0048] Test verification: 1. Dispersion stability test: (1) Standing sedimentation test: Standing at 60°C for 30 days and observing the sedimentation; (2) Centrifugal stability test: Centrifuge at 10,000 rpm for 30 minutes and measure the dispersed phase separation rate.

[0049] 2. Rheological properties test: measure the apparent viscosity at different shear rates, record the yield stress and thixotropy, and determine the dynamic viscoelasticity. Experimental conditions: (1) Temperature range: -20℃ to 120℃; (2) Shear rate: 0.1-1000 s⁻¹.

[0050] 3. Load-bearing capacity test: Four-ball machine extreme pressure performance test (GB / T 3142), record the maximum no-seizure load (PB), and measure the welding load (PD). Test conditions: (1) Speed: 1760rpm; (2) Time: 10s; Temperature: room temperature.

[0051] 4. Tribological performance test: reciprocating friction and wear test, record the change of friction coefficient, measure the wear scar size, and analyze the wear surface morphology. Test conditions: (1) Load: 50-500N; (2) Frequency: 25Hz; (3) Time: 2h; (4) Temperature: room temperature.

[0052] 5. Durability test: long-distance reciprocating friction test, monitoring the trend of friction coefficient change, and regularly sampling and analyzing oil performance. Test conditions: (1) load: 200N; (2) time: 100h; (3) temperature: 80℃.

[0053]

[0054] The test results of the wear-resistant lubricating oil performance of the embodiment group and the control group are shown in Table 1. Dispersion stability: Examples 1-5 all showed excellent dispersion stability, among which Examples 1 and 2 performed best, with static sedimentation rates of 0.6% and 0.5%, respectively, far better than 3.5% of the control group 1. This confirms the importance of the nanographene composite comb copolymer.

[0055] Rheological properties: The yield stress and thixotropic index of the example group are generally higher than those of the control group, indicating that the additive system forms a more stable three-dimensional network structure. Example 1 reaches the best value (yield stress 16.2 Pa).

[0056] Bearing capacity: The bearing capacity of Examples 1-5 is significantly better than that of the control group, wherein the welding load of Example 1 reaches 4000N, which is 42.9% higher than that of the control group 1 (2800N), reflecting the advantages of the three-layer protection structure.

[0057] Tribological properties: The example groups showed lower friction coefficient and smaller wear scar width. The average friction coefficient of Example 1 was only 0.062, and the wear scar width was 0.40 mm, which was better than all the control groups.

[0058] Durability: The example group showed excellent stability in the 100-hour durability test, and the friction coefficient growth rate and oil degradation rate were much lower than those of the control group. The performance of Example 1 was the most stable, with a friction coefficient growth rate of only 8.2%.

[0059] In summary, Example 1 exhibits the best comprehensive performance, which is due to the most reasonable distribution ratio of each component in its formula, which can give full play to the synergistic effect of the three-layer protection structure. The lack of any key component, as shown in Control Groups 1-4, will lead to a significant decrease in performance.

[0060] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A wear-resistant lubricating oil, characterized in that: The invention comprises the following raw materials in parts by weight: 50-55 parts of PAO (poly alpha olefin) synthetic oil, 8-10 parts of esterified castor oil-sucrose ester, 3-5 parts of octylphenol, 2-3 parts of molybdenum dithiocarbamate, 3-4 parts of sulfided isobutylene, 2-3 parts of zinc dialkyl dithiophosphate, and 2-3 parts of calcium sulfonate; The esterified castor oil-sucrose ester is an amphiphilic complex having both hydrophilicity and hydrophobicity formed by connecting the carboxyl group of the esterified castor oil and the hydroxyl group of the sucrose ester through an esterification reaction.

2. A wear-resistant lubricating oil as claimed in claim 1, characterized in that: Calculated by weight, it also includes: 2 to 4 parts of nanographene composite comb copolymer; The comb-shaped copolymer in the nano-graphene composite comb-shaped copolymer is formed by polymerization of methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate.

3. A wear-resistant lubricating oil as claimed in claim 2, characterized in that: The preparation method of the nano-graphene composite comb-shaped copolymer comprises: S11. washing methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with 5% sodium hydroxide solution to obtain washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, drying the washed methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate with anhydrous magnesium sulfate to obtain dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate, and distilling the dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate under reduced pressure to obtain purified dried methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate; S12. The purified methyl methacrylate and polyethylene glycol methanol monomethyl ether methacrylate were dissolved in tetrahydrofuran to obtain a first solution, azobisisobutyronitrile was added to the first solution to obtain a second solution, nitrogen was introduced into the second solution, and the reaction was carried out at 65 to 75 ° C for 24 to 36 hours to obtain a first reaction solution; S13. The first reaction solution is poured into an excess of cold ether to precipitate to obtain a first precipitate, and the first precipitate is vacuum dried to obtain a comb-like copolymer; S14. Adding flake graphite to a mixture of concentrated sulfuric acid and concentrated nitric acid to obtain a second mixed solution, slowly adding KMnO4 to the second mixed solution under ice bath conditions to obtain a second reaction solution, reacting the second reaction solution at 35-45 ° C for 2-3 h, then heating to 95-105 ° C for 30-40 min to obtain a third reaction solution, adding deionized water and hydrogen peroxide to the third reaction solution to terminate the reaction, and obtaining a fourth reaction solution; S15. centrifuging the fourth reaction solution to obtain a centrifuged reaction solution, washing the centrifuged reaction solution to neutrality to obtain a washed reaction solution, and ultrasonicating the washed reaction solution to obtain graphene oxide; S16. Disperse graphene oxide in tetrahydrofuran and perform ultrasonic treatment for 2 to 3 hours to obtain a graphene dispersion, dissolve the comb-like copolymer in tetrahydrofuran to obtain a comb-like copolymer solution, slowly drop the comb-like copolymer solution into the graphene dispersion to obtain a total dispersion, first ultrasonically disperse the total dispersion for 30 to 40 minutes to obtain a total dispersion after ultrasonication, magnetically stir the total dispersion after ultrasonication for 12 to 24 hours to obtain a total dispersion after magnetic stirring, filter the total dispersion after magnetic stirring to obtain a product, and vacuum dry the product to obtain a nano-graphene composite comb-like copolymer.

4. A wear-resistant lubricating oil according to claim 1, characterized in that: The preparation method of the esterified castor oil-sucrose ester comprises: S21. The castor oil is dried under vacuum at 60-70°C for 4-5h to obtain dried castor oil; S22. The dried castor oil was added to a three-necked flask, and then a 30 wt % KOH methanol solution was added to obtain a first mixed solution, nitrogen was introduced, and the first mixed solution was reacted at 65 to 75 ° C and 400 to 500 rpm for 4 to 5 h to obtain a first reaction solution; S23. The first reaction solution was cooled to room temperature, petroleum ether was added for extraction to obtain an extracted first reaction solution, the extracted first reaction solution was washed with distilled water for 3 to 4 times to obtain a washed first reaction solution, the washed first reaction solution was dried with anhydrous sodium sulfate to obtain a dried first reaction solution, the dried first reaction solution was rotary evaporated to obtain esterified castor oil; S24. The esterified castor oil is dissolved in dichloromethane to obtain an esterified castor oil solution, and sucrose ester is added to the esterified castor oil solution at a temperature of -5 to 0°C to obtain a second mixed solution; S25. In the second mixed solution, N, N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in dichloromethane were slowly added dropwise, stirred at 0 ° C for 1 h to obtain a third mixed solution, and the third mixed solution was heated to room temperature and the reaction was continued for 24 to 36 h to obtain a second reaction solution; S26. The second reaction liquid is subjected to reduced pressure distillation to obtain a second reaction liquid after reduced pressure distillation, the second reaction liquid after reduced pressure distillation is purified by column chromatography, the stationary phase is silica gel, and the mobile phase is petroleum ether / ethyl acetate to obtain a purified product, the purified product is rotary evaporated to obtain a rotary evaporated product, and the rotary evaporated product is vacuum dried to obtain the final product, i.e., esterified castor oil-sucrose ester.

5. A method for preparing a wear-resistant lubricating oil, used for preparing the wear-resistant lubricating oil as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: S31. The PAO (poly alpha olefin) synthetic oil was added to the reactor, heated to 60 ~ 70 ° C, stirring speed of 1000 ~ 1500rpm, to obtain pretreated PAO (poly alpha olefin) synthetic oil, the pretreated PAO (poly alpha olefin) synthetic oil was vacuum treated for 10 ~ 15min to obtain vacuum treated PAO (poly alpha olefin) synthetic oil; S32. Esterified castor oil - sucrose ester and octylphenol are sequentially added to the vacuum treated PAO (poly alpha olefin) synthetic oil, and stirred at 65 to 70 ° C and 1000 to 1500 rpm for 30 to 35 min to obtain a first mixed solution; S33. Molybdenum dithiocarbamate and isobutylene sulfide were sequentially added to the first mixed solution, and stirred at 80 to 85 ° C, 1500 to 2000 rpm for 30 to 35 min to obtain a second mixed solution; S34. Zinc dialkyl dithiophosphate and calcium sulfonate were sequentially added to the second mixed solution, and stirred at 80 to 85 ° C and 2000 to 2500 rpm for 30 to 35 min to obtain a third mixed solution; S35. Adding the nanographene composite comb copolymer to the third mixed solution, ultrasonically treating at 70 to 75° C. and 3000 to 4000 rpm for 15 to 30 min to obtain a fourth mixed solution; S36. In the fourth mixed solution, vacuum treatment is performed at 70 to 75° C. and 1500 to 2000 rpm for 15 to 20 min to obtain a vacuum-treated solution; S37. Cool the vacuum-treated solution to 45-50° C. to obtain a cooled solution, filter the cooled solution through a 100-mesh filter to obtain a sieved solution, and allow the sieved solution to stand for 24-36 hours to obtain a wear-resistant lubricating oil.

Citation Information

Cited By

  • High-temperature-resistant high-antifriction lubricating oil and preparation method thereof

    CN122381864A